SEGMENTATION OF MSMEs BASED ON FINANCIAL MANAGEMENT PATTERNS (Case Study of MSMEs in the Industrial Sector in Rantepao District) - Kondo, Marlina; Marchelin, Marchelin; Kurniasari Wibisono, Lisa (JURNAL EKBIS, 2025)
This study uses a quantitative research approach with the aim of analyzing the segmentation of MSMEs based on financial management patterns in the Rantepao District. Using a clustering method with the K-Means algorithm, this study groups MSMEs based on the characteristics of financial recording, planning, reporting, and control that are implemented. The results show that there are two main clusters: the first cluster (68%) consists of MSMEs that still use manual financial recording, have unclear financial planning, and lack structured financial control. Meanwhile, the second cluster (32%) consists of MSMEs that have adopted more systematic financial recording with tools such as Microsoft Excel or accounting applications, and have regular financial reports and better cash reserves. Based on these results, interventions are needed in the form of financial literacy training, access to digital recording technology, and mentoring for MSMEs to improve financial stability and long-term sustainability.